North‐South Asymmetric Kelvin‐Helmholtz Instability and Induced Reconnection at the Earth's Magnetospheric Flanks. Issue 11 (22nd November 2018) - Fadanelli, S.; Faganello, M.; Califano, F.; Cerri, S. S.; Pegoraro, F.; Lavraud, B.
Abstract: We present a three‐dimensional study of the plasma dynamics at the flank magnetopause of the Earth's magnetosphere during mainly northward interplanetary magnetic field periods. Two‐fluid simulations show that the initial magnetic shear at the magnetopause and the field line bending caused by the dynamics itself (in a configuration taken as representative of the properties of the flank magnetopause) influence both the location where the Kelvin‐Helmholtz (KH) instability and the induced magnetic reconnection take place and their nonlinear development. The KH vortices develop asymmetrically with respect to the Earth's equatorial plane where the local KH linear growth rate is maximal. Vortex‐driven reconnection processes take place at different latitudes, ranging from the equatorial plane to midlatitude regions but only in the hemisphere that turns out to be the less KH unstable. These results suggest that KH‐induced reconnection is not limited to specific regions around the vortices (inside, below, or above) but may be triggered over a broad and continuous range of locations in the vicinity of the vortices. Key Points: Three‐dimensional two‐fluid simulations including of Kelvin‐Helmholtz instability including high‐latitude stabilization Detailed analysis of the north‐south asymmetric development of the Kelvin‐Helmholtz instability Detailed analysis of the north‐south asymmetric development of magnetic reconnection induced by the Kelvin‐Helmholtz vortices